The sympathizer - Nguyen, Viet Thanh, 1971- (New York : Grove Press, 2015)
Follows a Viet Cong agent as he spies on a South Vietnamese army general and his compatriots as they start a new life in 1975 Los Angeles.
Keywords: Soldiers -- Vietnam (Republic) -- Fiction; Communists -- Vietnam (Republic) -- Fiction; Vietnam War, 1961-1975 -- Fiction; Spy stories; Historical fiction